Examining The Impact Of Air Pollution On Respiratory Illnesses In Urban Areas Of Saudi Arabia - Abdulaziz Ali Ahmed Alghamdi, Hanouf Khalid Aljuaid, Mohammed Mohsen Alzhrani & Abdullah Hameed Almalki (Migration Letters, 2022)
Air pollution is a persistent environmental and public health issue that affects populations globally. In recent years, the rapid industrialization and urbanization of Saudi Arabia has led to a significant increase in air pollution levels in its urban areas. This has raised concerns about its potential impact on respiratory health in the population. This qualitative review paper aims to examine the impact of air pollution on respiratory illnesses in urban areas of Saudi Arabia. It seeks to identify the various sources of air pollution in urban areas and understand how the[1]se contribute to respiratory illnesses. Additionally, it will explore the current government policies and initiatives aimed at reducing air pollution levels and their effectiveness. The review process involved a thorough analysis of existing literature, including research studies, government reports, and other relevant sources. Our findings suggest that air pollution in urban areas of Saudi Arabia is mainly caused by industrial activities, transportation, and household activities. These pollutants have been linked to various respiratory illnesses, including asthma, chronic obstructive pulmonary disease (COPD), and lung cancer, which have become major public health concerns in the country. Moreover, our review highlights that the implementation of stricter regulations and policies by the government has shown some promising results in reducing air pollution levels. However, there are still challenges in enforcing these regulations effectively. Additionally, there is a lack of awareness and understanding among the public about the health risks associated with air pollution, which calls for more education and public health initiatives. In conclusion, this qualitative review sheds light on the key factors contributing to air pollution and its impact on respiratory health in urban areas of Saudi Arabia. It highlights the need for further research and evidence-based interventions to address this issue and protect public health.